Ocular prosthesis modification with permanent soft liner in anopthalmic socket post evisceration - Leo, Andri C.; Syafrinani; Putri WU. Ritonga (Indonesian Journal of Prosthodontic, 2025)
Background: Enucleation and eviseration are surgical procedures often used for the removal of the eye. Some post-eviserated patients have complaints of discomfort when using conformer or ocular prosthesis. Ocular prosthesis modified with permanent soft liner (PSL) on the intaglio surface is an alternative to reduce the discomfort. Objective: This case report aims to explain the use of PSL in the manufacture of custom ocular prostheses in post-eviscerated patient. Case report: A 72-year-old male patient came to RSGM USU complaining of difficulty to socialize because he lost his eye and wanted to make a prosthetic. The patient had evisceration 4 months ago and was given a silicone surgical conformer. Tearing was the common complaint, followed by itchiness, soreness and uncomfortable when the conformer is fitted. Custom ocular prosthesis is modified using PSL on the intaglio surface. The use of PSL provides comfort to patients because it acts as a shock absorber and shock distributor that can distribute pressure more evenly so that the tissue in the eye socket receives less impact force. Conclusion: Fabrication of new ocular prosthesis with PSL is a novel way to minimize trauma to underlying supporting tissues so it can reduce the discomfort of the patient.Keywords: Evisceration, Custom ocular prosthesis, Permanent soft liner